Implementation of Cooperative Model's Jigsaw to Improve Mathematic Ability of Students - Sihite, Muda Sakti Raja (Proceedings International Conference on Education Innovation and Social Science, 2023)
The problem of this research is the low ability of mathematical connections due to the low ability of students to understand mathematical concepts. This research is a Classroom Action Research conducted at Husni Thamrin High School Medan. In the implementation of this research tools and research instruments have been developed. The results in cycle I show that: (1) the average test score of students' mathematical connection ability is 68.0 or there are 73% of the number of students who take the test have a level sis mathematical ability, (2) the level of active activity of students has not met the set ideal percentage of time, . In cycle II the results were obtained: (1) the average score of students' mathematical ability test was 73.0 or there were 86.6% of the number of students who took the test had a minimum level of students' mathematical ability in the sufficient category and 13.4% had a level students' mathematical are under the sufficient category, (2) the level of active activity of students fulfills the ideal percentage of time. In cycles I and II, concluded that implementation of jigsaw cooperative learning can improve students' mathematical ability.